Use of rubber tree (Hevea brasiliensis) latex biomembrane in diaphragmatic injuries in rabbits - an experimental study - Friolani, Milena [UNESP] (2011)
The aim of this study was to evaluate the surgical use of the natural latex biomembrane in diaphragmatic injuries produced experimentally in rabbits. Fifteen healthy adult male and female New Zealand rabbits were employed. The rabbits were assigned to the experimental groups I, II, III, IV and V and analyzed on the 15th, 30th, 45th, 60th and 90th days post surgery, respectively. The surgical procedure consisted in the access to the diaphragm at the eighth right intercostal space, removal of a circle portion of approximately 1.5 cm in diameter following surgical repair with a latex membrane. Macroscopically, it was observed an excellent healing process during the experimental period. The clinical observations, complemented by the histological analysis, indicate that the latex membrane is useful for repair of traumatic inuries of the diaphragm of rabbits.